Beyond naturalness : rethinking park and wilderness stewardship in an era of rapid change - Cole, David N.; Yung, Laurie, 1969- (Island Press, 2010)
The central concept guiding the management of parks and wilderness over the past century has been "naturalness"--To a large extent the explicit purpose in establishing these special areas was to keep them in their "natural" state. But what does that mean, particularly as the effects of stressors such as habitat fragmentation, altered disturbance regimes, pollution, invasive species, and climate change become both more pronounced and more pervasive? Beyond Naturalness brings together leading scientists and policymakers to explore the concept of naturalness, its varied meanings, and the extent to which it provides adequate guidance regarding where, when, and how managers should intervene in ecosystem processes to protect park and wilderness values. The main conclusion is the idea that naturalness will continue to provide an important touchstone for protected area conservation, but that more specific goals and objectives are needed to guide stewardship. The issues considered in Beyond Naturalness are central not just to conservation of parks, but to many areas of ecological thinking-including the fields of conservation biology and ecological restoration-and represent the cutting edge of discussions of both values and practice in the twenty-first century. This book offers excellent writing and focus, along with remarkable clarity of thought on some of the difficult questions being raised in light of new and changing stressors such as global environmental climate change